2021
DOI: 10.3389/fnins.2021.738408
|View full text |Cite
|
Sign up to set email alerts
|

Neural Measures of Pitch Processing in EEG Responses to Running Speech

Abstract: Linearized encoding models are increasingly employed to model cortical responses to running speech. Recent extensions to subcortical responses suggest clinical perspectives, potentially complementing auditory brainstem responses (ABRs) or frequency-following responses (FFRs) that are current clinical standards. However, while it is well-known that the auditory brainstem responds both to transient amplitude variations and the stimulus periodicity that gives rise to pitch, these features co-vary in running speec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 57 publications
(113 reference statements)
1
21
0
Order By: Relevance
“…It must be noted that although the wave V peak was used as the primary metric of performance, the conventional click ABR consists of several other morphological features [36]. The wave V peak was selected here to both be consistent with prior work [6, 19, 16], and because it was the only consistent feature that was detected in all subjects. TRFs using ZIL had shorter wave V peak latencies (see Figures 1 and 3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It must be noted that although the wave V peak was used as the primary metric of performance, the conventional click ABR consists of several other morphological features [36]. The wave V peak was selected here to both be consistent with prior work [6, 19, 16], and because it was the only consistent feature that was detected in all subjects. TRFs using ZIL had shorter wave V peak latencies (see Figures 1 and 3).…”
Section: Discussionmentioning
confidence: 99%
“…TRFs were estimated from EEG data recorded from 24 participants listening to continuous speech. Prior work indicates that the most prominent feature of subcortical TRFs is the wave V peak [6, 16]. This peak was used as the primary measure of performance in our study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…algorithm for computing the fundamental waveform was based on empirical mode decomposition (Huang and Pan, 2006;Forte et al, 2017). However, Etard et al (2019) showed that direct band-pass filtering of the speech signal is considerably simpler, faster to compute and leads to the same result (Kulasingham et al, 2020;Bachmann et al, 2021;Van Canneyt et al, 2021a,b). Here, we also employed a band-pass filter to extract the fundamental waveform from the voice recordings.…”
Section: Figurementioning
confidence: 99%
“…The original algorithm for computing the fundamental waveform was based on empirical mode decomposition (Huang and Pan (2006); Forte et al (2017)). However, Etard et al (2019) showed that direct band-pass filtering of the speech signal is considerably simpler, faster to compute and leads to the same result (Kulasingham et al (2020); Van Canneyt et al (2021b,a); Bachmann et al (2021)). Here, we also employed a band-pass filter to extract the fundamental waveform from the voice recordings.…”
Section: Methodsmentioning
confidence: 99%